PENERAPAN SISTEM PENDUKUNG KEPUTUSAN SELEKSI PEGAWAI TERBAIK DENGAN METODE MFEP DI DINAS PENDIDIKAN KABUPATEN JOMBANG - Rizky Permadi Syah; Setyo Permadi, Ginanjar; Andriani, Anita; Kistofer, Terdy (Fakultas Teknologi Informasi, 2024)
The Education and Culture Office of Jombang District implements a system of selecting the best employeesevery year to improve employee morale and reward their performance. Currently, the selection is donemanually, with subjective selection by the head of the office. This process takes a long time, and the resultsare subjective without standardized calculations. To improve accuracy and efficiency, a decision-makingsystem is needed that can assist in determining the best employees. One of the methods used is MFEP(Multi Factor Evaluation Process), with criteria such as work quality, responsibility, teamwork, discipline,and attendance. This method allows determining the weight of each attribute, ranking the suitability ofcriteria and alternatives, and ranking the best weighted data from several alternatives. Using the MFEPmethod and a sample of 36 employee data points, the highest value obtained is 8.8 and the lowest value is6.3. After calculation and ranking, a selection will be made to determine the best employee based on theranking value results.Keywords: best employee, selection method, decision-making system, ranking.